Establishment of a clinical cancer genetics program for breast cancer in a resource-limited country; challenges and opportunities - Abdel-Razeq, Hikmat; Sharaf, Baha; Tamimi, Faris; Hani, Hira Bani; Alsmadi, Osama; Khalil, Hanan; Abunasser, Mahmoud; Edaily, Sarah; Mansour, Asem (Frontiers in Oncology, 2024)
Breast cancer is the most common cancer among women worldwide, and its incidence rate is still increasing, especially among younger women. Nationally, it constitutes one-fifth of all cancer cases and almost 40% of all female cancers. With a median age of 51 years, breast cancer is diagnosed at least a decade earlier, and at more advanced stages compared to Western societies. Hereditary cancers account for 10% or more of all cancer burden worldwide. With expanded indications, increased number of genes tested, and significant decline in cost of testing, such proportion will probably increase. Individuals with pathogenic variants of BRCA1 and BRCA2 are at higher risk of breast, ovarian, pancreatic and many other cancers. Over the past two decades, several highly penetrant cancer-susceptibility genes were identified across almost all tumor sites, thus increasing the need for comprehensive cancer genetic programs that address the testing process, counselling patients and at-risk family members, and then deal with all testing results and its consequences. In addition to its important role in preventing more cancers in index patients themselves and among their close relatives, identification of pathogenic or likely pathogenic variants, mostly in BRCA1 or BRCA2, may inform therapeutic decisions in common cancers including breast, ovarian, prostate and pancreatic cancers. In this manuscript, we describe the experience of a comprehensive cancer center, in a resource-limited country in establishing a comprehensive clinical cancer genetics program that can serve as an example for others who share similar demographic and financial restrains.